Bacteriophage-mediated biosynthesis of MnO2NPs and MgONPs and their role in the protection of plants from bacterial pathogens - Ogunyemi, Solabomi Olaitan; Abdallah, Yasmine; Ibrahim, Ezzeldin; Zhang, Yang; Bi, Ji’an; Wang, Fang; Ahmed, Temoor; Alkhalifah, Dalal Hussien M.; Hozzein, Wael N.; Yan, Chengqi; Li, Bin; Xu, Lihui (Frontiers in Microbiology, 2023)
Xanthomonas oryzae pv. oryzae (Xoo) is the plant pathogen of Bacterial Leaf Blight (BLB) which causes yield loss of rice. Herein, the lysate of Xoo bacteriophage X3 was used to mediate the bio-synthesis of MgO and MnO2, which were characterized using conventional methods. Absorption peak of 215 and 230 nm for MgO and MnO2, respectively confirmed nanoparticles formation via UV-Vis. The physiochemical features of MgONPs and MnO2NPs were observed via Transmission/Scanning electron microscopy, X-ray diffraction, Energy dispersive spectrum and Fourier-transform infrared spectrum. Bacteriological tests indicated that MgONPs and MnO2NPs with the sizes of 12.5 and 9.8 nm, respectively, had strong in vitro antibacterial effect on rice bacterial blight pathogen, Xoo. MnO2NPs was found to have the most significant antagonist effect on nutrient agar plates while MgONPs had the most significant impact on bacterial growth in nutrient broth and on cellular efflux. Furthermore, no toxicity to plants was observed for MgONPs and MnO2NPs, indeed, MgONPs at 200 µg/ml significantly increased the quantum efficiency of PSII photochemistry on the model plant, Arabidopsis, in light (ΦPSII) compared to other interactions. Additionally, significant suppression of BLB was noted in rice seedlings amended with the synthesized MgONPs and MnO2NPs. MnO2NPs showed a promotion on plant growth in the presence of Xoo as compared to MgONPs. In summary, an effective alternative for biological production of MgONPs and MnO2NPs was reported which serves as an effective substitute to control plant bacterial disease with no phytotoxic effect.